2017
DOI: 10.1155/2017/6346912
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Evidence of Behavioral, Cognitive, and Psychiatric Endophenotypes in Autism: A Systematic Review

Abstract: Substantial evidence indicates that parents of autistic individuals often display milder forms of autistic traits referred to as the broader autism phenotype (BAP). To determine if discrete endophenotypes of autism can be identified, we reviewed the literature to assess the evidence of behavioral, cognitive, and psychiatric profiles of the BAP. A systematic review was conducted using EMBASE, MEDLINE, PsycINFO, PsycEXTRA, and Global Health. Sixty papers met our inclusion criteria and results are discussed accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 74 publications
0
8
0
2
Order By: Relevance
“…Our results show that behavioral flexibility and response inhibition ability are reduced in both probands and their parents and, importantly, that difficulty inhibiting prepotent responses is familial in ASD. While previous studies indicate the presence of a broader range of subclinical characteristics associated with ASD in unaffected parents than BAP traits alone (i.e., psychiatric, sensorimotor, and neuroanatomical features [18, 20, 42, 43];), this is the first known study to document the inter-correlation of a neurocognitive trait among individuals with ASD and their unaffected biological parents. This finding provides novel evidence that reductions in the ability to inhibit behavioral responses reflect a quantifiable dimension of inter-generational risk for ASD.…”
Section: Discussionmentioning
confidence: 85%
“…Our results show that behavioral flexibility and response inhibition ability are reduced in both probands and their parents and, importantly, that difficulty inhibiting prepotent responses is familial in ASD. While previous studies indicate the presence of a broader range of subclinical characteristics associated with ASD in unaffected parents than BAP traits alone (i.e., psychiatric, sensorimotor, and neuroanatomical features [18, 20, 42, 43];), this is the first known study to document the inter-correlation of a neurocognitive trait among individuals with ASD and their unaffected biological parents. This finding provides novel evidence that reductions in the ability to inhibit behavioral responses reflect a quantifiable dimension of inter-generational risk for ASD.…”
Section: Discussionmentioning
confidence: 85%
“…While estimates vary, there is general agreement that heritability is greater than 50%,42 with first degree relatives having a higher risk for developing autism relative to the general population. First degree relatives without a clinical diagnosis have a “broader autism phenotype” with subclinical traits similar to those seen in autism 4344. For example, later born siblings who do not have autism exhibit some autistic symptoms and lower levels of functioning compared with the general population 45…”
Section: Risk Factorsmentioning
confidence: 99%
“…Personality traits such as "cognitive rigidity" have been implicated in ASD, and may extend to first-degree relatives too. 12 Meta-analysis of the "Big 5" personality traits found that ASD was associated with lower openness, lower conscientiousness, lower extraversion, lower agreeableness, and lower emotional stability. 13 Further complicating this relationship between autistic traits and addiction is the fact that autistic traits commonly co-occur with ADHD symptoms, 14 which in turn also commonly co-occur with addictions such as problem gambling.…”
Section: Introductionmentioning
confidence: 99%